PENGARUH PENERAPAN ANGGARAN BERBASIS KINERJA DAN EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA APARATUR PEMERINTAH SATPOL PP DAN DAMKAR KABUPATEN TANAH DATAR - Meri Kurnia Sari; Andria Ningsih (Ensiklopedia Research and Community Service Review, 2026)
The performance of government officials is one of the key indicators in achieving effective, efficient, transparent, and accountable governance. In regional government agencies responsible for public services, law enforcement, public order, community protection, and fire management, such as theCivil Service Police Unit (Satuan Polisi Pamong Praja/Satpol PP)and theFire and Rescue Department (Damkar)of Tanah Datar Regency, improving officials' performance is essential and must be supported by high-quality regional financial management. Performance-based budgeting and the effectiveness of the internal control system are considered two important factors influencing the performance of government officials. Performance-based budgeting emphasizes the achievement of outputs and outcomes, while the internal control system ensures that organizational activities are carried out effectively, efficiently, in compliance with applicable regulations, and with minimal risk of irregularities. This study aims to examine the effect of performance-based budgeting and the effectiveness of the internal control system on the performance of government officials at the Civil Service Police Unit (Satpol PP) and Fire and Rescue Department (Damkar) of Tanah Datar Regency. This study employed a quantitative approach using a survey method by distributing questionnaires to all 40 government officials as respondents. A saturated sampling technique was applied, in which the entire population was included as the research sample. Data were analyzed using SmartPLS version 4 through measurement model (outer model), structural model (inner model), and hypothesis testing. The results indicate that performance-based budgeting has a positive and significant effect on the performance of government officials. In addition, the effectiveness of the internal control system also has a positive and significant effect on the performance of government officials. These findings suggest that better implementation of performance-based budgeting and more effective internal control systems contribute to improving the performance of government officials at the Civil Service Police Unit (Satpol PP) and Fire and Rescue Department (Damkar) of Tanah Datar Regency.Keywords: Performance-Based Budgeting, Internal Control System, Government Officials' Performance